You are Here: Home

# P2 Logs Please Quick Help watch

Announcements
1. 6^2x-1 = 9^x+3
(2x-1)lg6 = (x+3)lg9
2. Put all the x terms on the left and the other terms on the right.

Full solution below:
.
.
.
.
.
.
.
.
.
.
.

.
.
.
.
.
.
.
.
.
.
.
.
.
.
.
.
.
(2x-1)lg6 = (x+3)lg9
2x lg6 - lg6 = x lg9 + 3lg9
x (2 lg6 - lg9) = 3 lg9 + lg6
x = (3 lg9 + lg6) / (2 lg6 - lg9).
3. If you want to work it out,

log2 X =(log10 X)/(log10 2)
4. (Original post by ORIGINAL)
6^2x-1 = 9^x+3
(2x-1)lg6 = (x+3)lg9
lg6=lg2+lg3 & lg9=lg3+lg3
Expand both sides, then put x on the same side.
You will get the result.
(sometimes you don't get a nice result, really.)

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: April 17, 2004
Today on TSR

### Uni league tables

Do they actually matter?

### University open days

• University of Warwick
Sat, 20 Oct '18
• University of Sheffield
Sat, 20 Oct '18
• Edge Hill University
Faculty of Health and Social Care Undergraduate
Sat, 20 Oct '18
Poll

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE